Building a City in the Sky. (10th February 2023) - Karimi, Honeiah; Sañosa, David Joshua; Hernandez Rios, Kevin; Tran, Phoebe; Chun, Dorothy M; Wang, Richert; Arya, Diana J
Abstract : The conceptualization of multiliteracies initiated by the New London Group (NLG, 1996) emphasized the situated nature of language use as a socially complex network of multimodal engagement. Inspired by this view of language and literacy, computer-assisted language learning and second language acquisition scholars have advocated for a broader scope of second language learning to include the development of multiliteracies (Reinhardt & Thorne, 2019; Warner & Dupuy, 2018). In this conceptual article, we explore the potential affordances of immersive virtual reality (IVR) for the development of multiliteracies. As we attempt to construct a working theory of IVR as a catalyst for understanding and creating multiple forms of language in use, we draw on existing literature as well as on data from our multi-year study of multilingual adolescents engaging in multimodal activities using the Meta Quest headset. The interactions between adolescents and researchers were designed to maximize key IVR affordances (embodied cognition, presence, agency, and contextualization), and examples from the IVR sessions suggest how the adolescents are developing multiliteracies. We conclude with ideas for future research that focus on empowering L2 learners to express themselves as they develop the necessary knowledge and skills to engage in multimodal literacies.